REPRESENTASI DAMPAK PENINDASAN TOKOH DALAM NOVEL PAYA NIE KARYA IDA FITRI: PERSPEKTIF HEGEMONI ANTONIO GRAMSCI - Sahputra, Verdyan; Bisarul Ihsan; Laila Tri Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Practices of hegemony in Indonesia whether through government regulations that harm the public, a cultural legacy that normalizes injustice, or everyday forms of domination such as silencing and coercion have led to oppression being accepted as normal or “common sense.” This study aims to describe the psychological and social impacts of the oppression of characters in Ida Fitri’s novel Paya Nie from the perspective of Antonio Gramsci’s theory of hegemony. The method used is qualitative descriptive analysis grounded in Gramsci’s theory of hegemony, utilizing textual data from the novel Paya Nie. The results show that oppression causes trauma, fear, despair, and deep emotional wounds, and has social consequences such as stigma, the loss of solidarity, the breakdown of family structures, and the erosion of public trust. These impacts arise not only from physical violence but are also reinforced by ideologies and cultural norms that normalize domination as a natural state. The novel Paya Nie thus illustrates how hegemony operates on multiple levels in the daily lives of the Acehnese people during the conflict. This study underscores the role of literature as a critical medium for revealing the consequences of hegemony while fostering awareness of the importance of science and knowledge in combating oppression.